Exploring the key behavioural, functional and strategic competencies in Indian management education - Shukla, Nidhi; Prasad, S K; Itam, Urmila (International Journal of Financial, Accounting, and Management, 2021)
Purpose: The study’s primary purpose is to identify the critical sustainable competencies and their importance in Indian management education perceived by the stakeholders. Research Methodology: The study adopted an explanatory research design and a standardised questionnaire to gather data from stakeholder groups. Results: The results suggest that the competency clusters considered necessary by the main stakeholder groups are behavioural, functional and strategic. Limitations: Broader perspective with more samples at various locations will add more value to the idea. Contribution: This paper aims to support both business and academia by recommending a positive collaborative process and building a workforce ready for work.